Rib hyperostosis: a benign entity with suspicious imaging features - Michael W. O'Bryant, DO; Rickhesvar P. Mahraj, MD; Thomas W. Allen, MD; Donald J. Flemming, MD (Radiology Case Reports, 2022)
Rib hyperostosis has previously been described in conjunction with disorders causing excessive vertebral ossification due to osseous bridging across the costovertebral joint, such as in diffuse idiopathic skeletal hyperostosis. Hyperostosis is believed to be a reactive process due to altered forces across the affected rib as bridging osteophytes decrease mobility at the respective costovertebral joint. The imaging characteristics of rib hyperostosis can be highly suspicious for malignancy. We share 2 cases of biopsy-proven benign rib hyperostosis with imaging across multiple modalities in hopes of increasing awareness of this entity and its imaging characteristics. In the first case, a 62-year-old female without history of malignancy underwent rib biopsy after bone scintigraphy demonstrated intense radiotracer uptake along a posteromedial rib. In the second case, a 66-year-old male with history of recurrent prostate cancer underwent rib biopsy after interval development of intense radiotracer uptake on bone scintigraphy along a posteromedial rib, new compared to 6 months prior. Both cases were seen in the setting of osseous bridging at the respective costovertebral joint. Imaging findings include contiguous radiotracer uptake on bone scintigraphy confined to the rib and respective costovertebral joint, cortical bone thickening with osseous excrescence at the costovertebral joint on radiographic and cross-sectional imaging, and increased osseous edema-like change, postcontrast enhancement, and surrounding soft tissue edema on magnetic resonance imaging. By increasing awareness to these imaging features, we hope to improve diagnostic confidence and decrease unnecessary, expensive, and sometimes invasive workup for future patients.